2020
DOI: 10.1016/j.optcom.2019.124786
|View full text |Cite
|
Sign up to set email alerts
|

Invariance property in scattering media and absorption

Abstract: In this paper we deal with the influence on absorption of the diffusive media characteristics framing the problem in connection with the invariance property (IP) of the mean path length. We show that the IP is an important issue that regulates but not prevent the search of absorption maximization by scattering characteristics. We find that the scattering may increase the absorption or even be detrimental, depending on the geometry of the medium and the conditions of its illumination.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…These processes encompass very different fields, involving different particles or different kinds of entities that undergo random walks during their propagation through a medium. In physics, transport processes are fundamental, for instance, in tissue optics 1 10 atmospheric physics 11 , 12 , neutron scattering 13 , 14 random laser 15 17 , lévy glass 18 , photovoltaic 19 22 , and sensing 23 25 . In biology, they include random walks of animals 26 and epidemic spreads 27 , whereas in sociology, the random walk emerges in phenomena such as the human migration 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes encompass very different fields, involving different particles or different kinds of entities that undergo random walks during their propagation through a medium. In physics, transport processes are fundamental, for instance, in tissue optics 1 10 atmospheric physics 11 , 12 , neutron scattering 13 , 14 random laser 15 17 , lévy glass 18 , photovoltaic 19 22 , and sensing 23 25 . In biology, they include random walks of animals 26 and epidemic spreads 27 , whereas in sociology, the random walk emerges in phenomena such as the human migration 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Equation ( 1 ) is thus also valid in presence of scattering inhomogeneities in the medium 56 and also for refractive index mismatches between different regions of the propagation domain 52 , 55 . Also known as “Cauchy’s formula”, the invariance property has been studied in different contexts, such as nuclear physics 56 , 57 and optics 22 , 52 , 58 , and has been recently experimentally verified for light propagation through scattering media 53 and for bacterial random walks 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Path length distributions and mean path length are central to the design of many optical systems where a ray optics description can be used. They can be used for calculating the optical properties of absorbing and scattering media [6,7], refractive granular media in pharmaceutical powders [8], for solar cell design [9][10][11], random lasing [12], and integrating spheres [13,14]. Ray tracing can also be combined with diffraction effects to calculate the electromagnetic scattering properties of large particles in models such as the geometric optics approximation and physical optics model [15][16][17][18][19][20], or anomalous diffraction theory [21][22][23].…”
mentioning
confidence: 99%
“…The IP remains valid also in case of a infinitely extending medium, such as a thin slab, and with different values of the asymmetry factor g of the scattering function [28].…”
Section: Introductionmentioning
confidence: 95%
“…Light scattering in optical media is a research field that involves a wide range of different theoretical and experimental issues, such as light propagation in biological tissue [1][2][3][4], random lasers [5][6][7][8][9], Anderson localization [10,11], anomalous diffusion [12][13][14], and replica symmetry breaking phenomena [15][16][17]. Moreover, concerning the applications, light diffusion has also been studied in optical sensing [18][19][20][21][22] and to find new design for solar cells in order to enhance the absorption effects [23][24][25][26][27]; in this regard, it has been reported that a small amount of scattering can promote the absorption in a thin slab subjected to monodirectional illumination [28].…”
Section: Introductionmentioning
confidence: 99%